Prostate cancer: a comparison of the diagnostic performance of transrectal ultrasound versus contrast enhanced transrectal ultrasound in different clinical characteristics - Li, Hongli (Int J Clin Exp Med, 2015)
To determine whether contrast-enhanced transrectal ultrasound (CE-TRUS) is superior to transrectal ultrasound (TRUS) on diagnosis of prostate cancer, 317 patients were processed TRUS examination with or without SonoVue, then biopsy was performed. Sensitivity, specificity, accuracy, positive predictive value (PPV) and negative predictive value (NPV) of two techniques were compared in multiple subgroups of PSA level, Digital rectal examination (DRE) and prostate volume on biopsy results. In PSA 4-10 ng/ml and DRE negative groups, CE-TRUS had greater sensitivity and accuracy compared with TRUS by patient (P = .004 and .003; .013 and .005 respectively) and greater sensitivity, accuracy, PPV and NPV by core. When prostate volume was 45-65 ml, CE-TRUS had greater specificity and accuracy by patient and all diagnostic performances were statistically significant by core. CE-TRUS is superior to TRUS on diagnosis of prostate cancer in a designed patient population with lower PSA level, DRE negative findings and modest prostate volume.